2013
DOI: 10.1097/qad.0b013e32835faa72
|View full text |Cite
|
Sign up to set email alerts
|

The CD4/CD8 ratio as a marker T-cell activation, senescence and activation/exhaustion in treated HIV-infected children and young adults

Abstract: We explored the associations of the CD4/CD8 ratio with markers of immunoactivation, immunosenescence and T-cell subsets, in 37 vertically HIV-infected children and adolescents. CD4/CD8 ratio inversion was associated with higher frequencies of activated, senescent and activated/exhausted CD4+ and CD8+ T-cells, and a skewed T-cell phenotype from naive toward effector memory which persisted after the multivariate analysis. Thus, the CD4/CD8 ratio may identify patients with higher immunoactivation despite ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 17 publications
7
110
1
3
Order By: Relevance
“…Today, it is widely known that in many cases, despite fully recovered CD4 counts after long-term ART, the CD4/CD8 ratio rarely reaches normal levels. The reason for this is unknown, but recent data from HIV-infected children, adolescents, and adults who were receiving ART have shown strong associations between the CD4/CD8 ratio and T cell activation, senescence, and activation/ exhaustion (23,24). All of our diverse analyses confirm that the CD4/CD8 ratio is a better surrogate of combined T cell pathogenesis than the CD4 count and VL.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Today, it is widely known that in many cases, despite fully recovered CD4 counts after long-term ART, the CD4/CD8 ratio rarely reaches normal levels. The reason for this is unknown, but recent data from HIV-infected children, adolescents, and adults who were receiving ART have shown strong associations between the CD4/CD8 ratio and T cell activation, senescence, and activation/ exhaustion (23,24). All of our diverse analyses confirm that the CD4/CD8 ratio is a better surrogate of combined T cell pathogenesis than the CD4 count and VL.…”
Section: Discussionsupporting
confidence: 52%
“…Recent data from both HIV-infected children and adults have shown strong associations between the CD4/CD8 ratio and T cell activation, senescence, and activation/exhaustion in patients receiving ART (23,24). However, multiparametric analyses that combine memory CD4 + and CD8 + T cell activation, exhaustion, and senescence markers have not been conducted and correlated with the currently measured routine laboratory parameters.…”
mentioning
confidence: 99%
“…This is important as incomplete recovery of CD4/CD8 ratio is associated with increased mortality and morbidity during HIV infection [8].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the setting of normal CD4 + counts among treated HIV-infected persons, low CD4/CD8 is associated with poor clinical outcomes [5,6], T-cell dysfunction [6][7][8], and increased inflammation (eg, interleukin 6, C-reactive protein, soluble CD14) [6,9]. These data suggest that CD8 + T-cell expansion might be a driver of increased morbidity and mortality [6,10].…”
mentioning
confidence: 99%
“…34 Allers et al found an increased effector memory phenotype in older HIV patients associated to an increased inflammatory cytokines. 6 The reduced CD4/CD8 ratio, 47 the decreased expression of CD28, the shift from na€ ıve to central memory cells and the reduction of TCR repertoire is much more evident in HIV-infected patients before the introduction of HAART. 8 However HAART is not able to normalize these phenomena.…”
Section: Immunology Of Aging In Hiv-infected Patientsmentioning
confidence: 99%